Research on macroeconomic intelligent decision system based on data mining - Zhang, Bei; Wang, Chunjuan; Yang, Xiaolei; Ren, Jia; Zhuang, Ming (Proceedings of SPIE, the international society for optical engineering, 2025)
In the rapid development of information technology in our country, the ability of each industry to obtain information is becoming stronger and stronger. How to carry on high-level analysis and efficient use in the rich and diverse information set is the main topic discussed by the academic circle. Under the development trend of economic globalization, data mining, as a new subject of development concern in the new era, can raise data application from simple query at the bottom level to knowledge mining and provide decision support. After understanding the basic concepts of macroeconomics and the current situation of decision-making, this paper defines the overall design of data mining module according to the application characteristics and operation process of data mining, and finally discusses the application effect of supporting limited integral class in macroeconomic forecasting, so as to provide strong support for economic decision-making in the new era.